2013
DOI: 10.1002/chem.201202811
|View full text |Cite
|
Sign up to set email alerts
|

Does Hydrogen‐Bonding Donation to Manganese(IV)–Oxo and Iron(IV)–Oxo Oxidants Affect the Oxygen‐Atom Transfer Ability? A Computational Study

Abstract: Iron(IV)-oxo intermediates are involved in oxidations catalyzed by heme and nonheme iron enzymes, including the cytochromes P450. At the distal site of the heme in P450 Compound I (Fe(IV) -oxo bound to porphyrin radical), the oxo group is involved in several hydrogen-bonding interactions with the protein, but their role in catalysis is currently unknown. In this work, we investigate the effects of hydrogen bonding on the reactivity of high-valent metal-oxo moiety in a nonheme iron biomimetic model complex with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
56
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 128 publications
(114 reference statements)
14
56
0
Order By: Relevance
“…The TS3 is 15.4 kcal/mol, showing that the additional water molecule in-fact destabilizes TS3 unlike reports elsewhere [59,60]. This result agrees with the study of de Visser et al in which hydrogen bonding interactions reduce the catalytic activity in Fe(IV)-oxo biomimetic complexes [61]. In addition, additional water molecules were predicted to increase the activation barrier of the PCET between close Tyr radical and Cys residues in the different peptide chains in protein molecules by model DFT calculations [41].…”
Section: Water Assisted Proton Shuttle Mechanismsupporting
confidence: 91%
“…The TS3 is 15.4 kcal/mol, showing that the additional water molecule in-fact destabilizes TS3 unlike reports elsewhere [59,60]. This result agrees with the study of de Visser et al in which hydrogen bonding interactions reduce the catalytic activity in Fe(IV)-oxo biomimetic complexes [61]. In addition, additional water molecules were predicted to increase the activation barrier of the PCET between close Tyr radical and Cys residues in the different peptide chains in protein molecules by model DFT calculations [41].…”
Section: Water Assisted Proton Shuttle Mechanismsupporting
confidence: 91%
“…As shown in Figure 5a, EER is observed for 4 but not for the more basic complexes 1 and 2 , which have much larger barriers. It is also worthy to note that the H-abstraction barriers of these basic oxidants with S1 are higher even than that of the analogous high spin [Fe IV OTMG 3 tren] 2+ oxidant (15.6 kcal/mol) 45 or of other Fe IV O complexes 5j,19 (Tables S20 and S21). The root cause of the higher HAT barriers for 1 and 2 is the significant basicity of these iron(IV)-oxo complexes.…”
Section: Discussionmentioning
confidence: 98%
“…Theoretical simulations of proximal pocket/sulfur hydrogen bonding in nitric oxide synthase showed that such bonding may affect the distribution of the thiolate/porphyrin unpaired spin [42]. The effect of hydrogen bonding to the distal oxygen of model manganese(IV)-oxo and iron(IV)-oxo oxidants on the oxidants’ ability for oxygen atom transfer was studied [43]. However, to the best of our knowledge, there are no published theoretical results regarding the possibility that the proximal helix and the NH–S bonds may affect the enantiospecificity of oxidations catalyzed by heme-thiolate enzymes.…”
Section: Introductionmentioning
confidence: 99%